It's the Situation and Your Disposition: A Test of Two Honesty Hypotheses. Issue 2 (March 2021) - Markowitz, David M.; Levine, Timothy R.
Research has documented substantial individual differences in the proclivity for honesty or dishonesty and that personality traits meaningfully account for variations in honesty–dishonesty. Research also shows important situational variation related to deception, as situations can motivate or discourage dishonest behaviors. The current experiment examines personality and situational influences on honesty–dishonesty in tandem, arguing that their effects may not be additive. Participants ( N = 114) engaged in an experimental task providing the opportunity to cheat for tangible gain. The situation varied to encourage or discourage cheating. Participants completed the HEXACO-100 and the Dark Triad of Personality scales. Both situational variation and personality dimensions predicted honesty–dishonesty, but the effects of personality were not uniform across situations. These results were also supported using public data from an independent, multilab sample ( N = 5, 757). We outline how these results inform our understanding of deception, situational influences, and the role of disposition in honesty.